Prenatal MRI diagnosis and outcomes of abdominal or sacrococcygeal teratomas and parasitic fetuses - Li, Xu; Lin, Hui hui; Hu, Ke fei; Peng, Yun (Frontiers in Pediatrics, 2023)
Objective To investigate the MRI findings of fetal abdominal or sacrococcygeal teratomas and parasitic fetuses and analyze the outcomes on the basis of follow-up assessments. Methods The MRI data of 60 cases of abdominal or sacrococcygeal masses were examined. The outcomes were followed up and compared with the prenatal MRI diagnoses. Results The 60 cases included 52 cases of sacrococcygeal teratomas and eight cases of abdominal lesions. The common types of sacrococcygeal teratomas were type I (21/52, 40.4%) and type II (20/52, 38.5%); type III sacrococcygeal teratomas were rarer (8/52, 15.4%), while type IV tumors (3/52, 5.7%) were frequently complicated with hydronephrosis. Other complications included polyhydramnios in 22 cases, placental edema in six cases, and fetal hydronephrosis in three cases (all type IV). Seven of the eight parasitic fetuses were located in the abdominal cavity, and one was located in the sacrococcygeal region. Postnatal surgery was performed in 51 cases (51/60), including 44 with teratomas and seven with parasitic fetuses. In one case with hydronephrosis, peritoneal effusion, and subcutaneous edema, treatment was discontinued after birth (1/60). Fetal induction of labor was observed in eight cases (8/60). Prenatal ultrasound yielded incorrect or ambiguous diagnoses in 11 cases, while 51 cases showed a favorable course after surgery. Conclusions MRI shows high accuracy in the diagnosis of fetal sacrococcygeal teratomas and parasitic fetuses. The prognosis in these cases is generally good. However, type IV sacrococcygeal teratomas are prone to fetal hydronephrosis and misdiagnosis and show a poorer prognosis.